Advances in Modern Diagnostic Methods and Antibiotic Susceptibility of Pseudomonas aeruginosa in Dogs: A Systematic Review - Maria Trisiana Dhue Nay (Journal of Tropical Animal Science and Technology, 2026)
Pseudomonas aeruginosa is a Gram-negative opportunistic bacterium that frequently causes infections in dogs and has a high capacity to develop antibiotic resistance. The high variability in resistance patterns, along with limited effective therapeutic options, makes accurate bacterial identification and the mapping of antibiotic susceptibility patterns essential for infection control. This study aimed to evaluate molecular identification methods as well as the patterns of antibiotic susceptibility and resistance of Pseudomonas aeruginosa reported in various studies using a Systematic Literature Review (SLR) approach. Literature searches were conducted in PubMed, Scopus, ScienceDirect, and Google Scholar databases based on predefined keywords and research questions. A total of 57 articles were initially identified, of which 21 met the inclusion criteria after the screening process using the Rayyan application. The results of the SLR showed that Pseudomonas aeruginosa is frequently isolated from dogs, with predominant sample types including ear swabs and wound swabs, as well as samples from urinary tract, respiratory tract, and pyoderma infections. Bacterial diagnosis was performed using conventional culture methods, along with the development of modern diagnostic approaches, including automated systems such as VITEK® 2 Compact, MALDI-TOF MS, and molecular methods based on PCR and Whole Genome Sequencing (WGS). The most commonly targeted genes for identification were the 16S rRNA gene, along with specific genes such as oprI and oprL. Antibiotic susceptibility patterns indicated that Pseudomonas aeruginosa is most frequently reported to exhibit high resistance to fluoroquinolones, followed by sulfonamides and other antibiotic classes. In contrast, carbapenems, antipseudomonal cephalosporins, and aminoglycosides still demonstrate relatively high levels of susceptibility